A Physiological Pattern of Oxygenation Using Perfluorocarbon-Based Culture Devices Maximizes Pancreatic Islet Viability and Enhances β-Cell Function. Issue 9 (September 2013) - Fraker, Chris A.; Cechin, Sirlene; Álvarez-Cubela, Silvia; Echeverri, Felipe; Bernal, Andrés; Poo, Ramón; Ricordi, Camillo; Inverardi, Luca; Domínguez-Bendala, Juan
Conventional culture vessels are not designed for physiological oxygen (O2 ) delivery. Both hyperoxia and hypoxia—commonly observed when culturing cells in regular plasticware—have been linked to reduced cellular function and death. Pancreatic islets, used for the clinical treatment of diabetes, are especially sensitive to sub- and supraphysiological O2 concentrations. A result of current culture standards is that a high percentage of islet preparations are never transplanted because of cell death and loss of function in the 24–48 h postisolation. Here, we describe a new culture system designed to provide quasiphysiological oxygenation to islets in culture. The use of dishes where islets rest atop a perfluorocarbon (PFC)-based membrane, coupled with a careful adjustment of environmental O2 concentration to target the islet physiological pO2 range, resulted in dramatic gains in viability and function. These observations underline the importance of approximating culture conditions as closely as possible to those of the native microenvironment, and fill a widely acknowledged gap in our ability to preserve islet functionality in vitro. As stem cell-derived insulin-producing cells are likely to suffer from the same limitations as those observed in real islets, our findings are especially timely in the context of current efforts to define renewable sources for transplantation.